Surgical intervention does not affect short-term plasma citrulline levels in infants: implications for citrulline as a marker of postoperative intestinal complications - Frongia, Giovanni; Romero, Philipp; Mehrabi, Arianeb; Holland-Cunz, Stefan; Günther, Patrick (European surgery, 2015)
Detection of intestinal ischemia is often delayed causing extensive complications. Serum citrulline is an important parameter for bowel integrity and functionality; however, no data is available on its response on postoperative intestinal impairment in children. The aim of this study was to evaluate the native effects of intestinal surgery on the postoperative citrulline course in children.
Gesehen am 30.06.2020